RARE VARIANTS IN THE CYP27B1 GENE ARE ASSOCIATED WITH MULTIPLE SCLEROSIS. (29th November 2012) - Ebers, G; Ramagopalan, SV; Dyment, DA; Cader, ZM; Disanto, G; Handel, A; DeLuca, GC; Sadovnick, AD; Lepage, P; Montpetit, A
Abstract : Multiple sclerosis (MS) is a complex neurological disease. Genetic linkage analysis and genotyping of candidate genes in families with four or more affected individuals more heavily loaded for susceptibility genes has not fully explained familial disease clustering. We performed whole exome sequencing to further understand the heightened prevalence of MS in these families. Forty-three individuals with MS (one from each family) were sequenced to find rare variants in candidate MS susceptibility genes. On average, >58 000 variants were identified in each individual. A rare variant in the CYP27B1 gene causing complete loss of gene function was identified in one individual. Homozygosity for this mutation results in vitamin D-dependent rickets I (VDDR1), whereas heterozygosity results in lower calcitriol levels. This variant showed significant heterozygous association in 3046 parent-affected child trios (p=1 ×10 5 ). Further genotyping in >12 500 individuals showed that other rare loss of function CYP27B1 variants also conferred significant risk of MS, Peto OR=4.7 (95% CI 2.3–9.4; p=5 ×10 −7 ). Four known VDDR1 mutations were identified, all overtransmitted. Heterozygous parents transmitted these alleles to MS offspring 35 of 35×(p=3×10 −9 ). A causative role for CYP27B1 in MS is supported; the mutations identified are known to alter function having been shown in vivo to result in rickets when two copies are present. CYP27B1 encodes the vitamin D-activating 1-α hydroxylase enzyme, and thus a role for vitamin D in MS pathogenesis is strongly implicated.